Constraints Faced by Pineapple Farmers in Adopting Climate Smart Adaptation Strategies in Kerala (Indian Journal of Extension Education, 2025)
The demand for pineapples is significant in Kerala, making sustainable cultivation crucial for long-term agricultural development. Ernakulam, Kottayam, and Kollam are among the key pineapple-producing districts in the state. However, pineapple farmers in these regions face numerous challenges in adopting climate-smart adaptation strategies. This study, conducted during May 2024, aimed to identify and prioritize these constraints using data collected from 130 farmers through personal interviews. Garrett’s ranking technique was employed to analyse the data. The findings revealed that market price fluctuations, often caused by reduced fruit weight due to adverse climatic conditions, were the most critical barrier. Other significant constraints included inadequate labour availability, insufficient government support, high input costs, limited agricultural subsidies, restricted access to climate-smart technologies, and inadequate credit facilities. This study emphasizes the need for improved marketing infrastructure, enhanced labour availability, stronger government support, and increased access to climate-smart technologies and financial resources. Addressing these barriers is vital to strengthening the adaptive capacity of pineapple farmers in Kerala and ensuring resilience and sustainability in the face of climate change.